Ease of Use of the Insulin Glargine 300 U/mL Pen Injector in Insulin-Naïve People With Type 2 Diabetes. (March 2017) - Pohlmeier, Harald; Berard, Lori; Brulle-Wohlhueter, Claire; Wu, Junlong; Dahmen, Raphael; Nowotny, Irene; Klonoff, David
Background: Insulin glargine 300 U/mL (Gla-300) contains the same active ingredient as glargine 100 U/mL (Gla-100), and provides the same number of units in one-third of the volume. The SoloSTAR ® injector pen has been modified to ensure accurate administration of this reduced volume and to improve user experience. Methods: Insulin- and pen-naïve adults with type 2 diabetes (T2DM) inadequately controlled with oral antihyperglycemic drugs, who had glycated hemoglobin (HbA1c) levels of 7.0-11.0 % (53-97 mmol/mol) were studied. They received once-daily Gla-300 in this 4-week, multicenter, open-label, single-arm study (NCT02227212). Ease of use/ease of learning (the primary endpoint), glycemic control, safety, and reliability of the disposable (prefilled) Gla-300 injector pen (secondary endpoints) were evaluated. Results: At week 4, 95.0% of 40 participating subjects assessed the pen as excellent/good and none as poor/very poor; 97.5% would recommend it to others. Total Diabetes Treatment Satisfaction Questionnaire scores were stable throughout the study. Mean (SD) fasting plasma glucose levels decreased from 166.1 (35.0) mg/dL at baseline to 124.2 (41.1) mg/dL at week 4. No product technical complaints (PTCs) or adverse events (AEs) related to PTCs were reported. The number of subjects experiencing hypoglycemic events of any kind and the incidence of AEs were low. No serious AEs were reported. Conclusions: The Gla-300 injector pen is easy to use and easy to learn to use, with demonstrable reliability and high degrees of acceptance and treatment satisfaction. Once-daily Gla-300 basal insulin treatment was well tolerated and effective in pen- and insulin-naïve adult T2DM subjects.